Aplikasi Pendataan Motor Second Berbasis Dekstop Pada CV. Win Motor Sungai Pinyuh - Panny Agustia Rahayuningsih; Bima Mukti Nugroho (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
In the current era of globalization, information technology is advancing rapidly. Computer technology is equipment that was created to facilitate human work, is currently making progress both in making hardware and software. CV. Win Motor is a company engaged in the sale of Second Motorcycles. Existing system in Cv. Win Motor is still carried out conventionally, starting from recording motor unit data, sales transactions, to making reports. So that store performance is ineffective and inefficient and allows errors in recording, especially when making reports. Therefore it requires the existence of an information system that supports and facilitates employees in carrying out their work, especially in sales activities every day. For this reason the author tries to make the Final Project on making a sales system on Cv. Win Motor which until now has not been computerized. The method used in making software, this design system uses the SDLC model of a waterfall. The design of this information system is the best solution to solve the problems that exist in this company, as well as with a computerized system can achieve an effective and efficient activity in supporting activities in this company.